The prediction of lambing rate in Awassi sheep using a rapid visual PAG ELISA test - Akköse, M; Çebi-Şen, Ç; Polat, Y (Journal of the Hellenic Veterinary Medical Society, 2022)
The accurrate diagnosis of pregnancy and prediction of lambing rate are important tools that ensure the proper nutrition of pregnant ewes, optimize the birth weight of offspring and decrease the occurrence of pregnancy toxemia in sheep production. In this study, it was aimed to evaluate the reliability of the rapid visual PAG ELISA test in predicting the lambing rate, when performed in two different stages of pregnancy in Awassi sheep. A total of 210 ewes, belonging to a commercial flock, were assigned to two groups according to their mating date. Group 1 comprised 120 ewes, which were in the period from 28 to 38 days post-mating, and Group 2 comprised 90 ewes, which were in the period from 40 to 59 days post-mating. The rapid visual PAG ELISA test was performed on the serum samples of the ewes, according to the manufacturer’s instructions. The diagnostic test characteristics of the rapid visual PAG ELISA test were assessed for the prediction of lambing rate, using the lambing records as a gold standard. The sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of the rapid visual PAG ELISA test were 95.79%, 52.38%, 90.10%, 73.33%, and 87.93%, respectively, in G1 and 92.75%, 70.00%, 91.43%, 73.68%, and 87.64%, respectively, in G2. The McNemar analysis showed that there was no difference between the rapid visual PAG ELISA test and lambing records in the two groups. Eighty per cent all of the ewes exposed to rams lambed. While the rapid visual PAG ELISA test predicted that 83.4% of the ewes exposed to rams would lamb, in reality it achieved that 75.6% of them lambed. The differences between the predicted and achieved lambing rates of rapid visual PAG ELISA (7.8%) indicate embriyonic/fetal mortality. The results of this study indicated that the lambing rate can be predicted with a high sensitivity from the 28th day of pregnancy, using the rapid visual PAG ELISA test.